Utility of Cement Augmentation via Percutaneous Fenestrated Pedicle Screws for Stabilization of Cancer-Related Spinal Instability. Issue 5 (3rd May 2019) - Barzilai, Ori; McLaughlin, Lily; Lis, Eric; Reiner, Anne S; Bilsky, Mark H; Laufer, Ilya
Abstract: BACKGROUND: Cancer patients experience pathological fractures and the typical poor bone quality frequently complicates stabilization. Methods for overcoming screw failure include utilization of fenestrated screws that permit the injection of bone cement into the vertebral body to augment fixation. OBJECTIVE: To evaluate the safety and efficacy of cement augmentation via fenestrated screws. METHODS: A retrospective chart review of patients with neoplastic spinal instability who underwent percutaneous instrumented stabilization with cement augmentation using fenestrated pedicle screws. Patient demographic and treatment data and intraoperative and postoperative complications were evaluated by chart review and radiographic evaluation. Prospectively collected patient reported outcomes (PRO) were evaluated at short (2- <6 mo) and long term (6-12 mo). RESULTS: Cement augmentation was performed in 216 fenestrated pedicle screws in 53 patients. Three patients required reoperation. One patient had an asymptomatic screw fracture at 6 mo postoperatively that did not require intervention. No cases of lucency around the pedicle screws, rod fractures, or cement extravasation into the spinal canal were observed. Eight cases of asymptomatic, radiographically-detected venous extravasation were found. Systemic complications included a pulmonary cement embolism, a lower extremity deep vein thrombosis, and a postoperative mortality secondary to pulmonary failure from widespread metastatic pulmonary infiltration. Significant improvement in PRO measures was found in short- and long-term analysis. CONCLUSION: Cement augmentation of pedicle screws is an effective method to enhance the durability of spinal constructs in the cancer population. Risks include cement extravasation into draining blood vessels, but risk of clinically significant extravasation appears to be exceedingly low.